2015
DOI: 10.1158/1535-7163.mct-14-0142
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Polypyrimidine Tract–Binding Protein 1 Expression in Colorectal Cancer

Abstract: Polypyrimidine tract-binding protein (PTBP1) is an RNAbinding protein with various molecular functions related to RNA metabolism and a major repressive regulator of alternative splicing, causing exon skipping in numerous alternatively spliced pre-mRNAs. Here, we have investigated the role of PTBP1 in colorectal cancer. PTBP1 expression levels were significantly overexpressed in cancerous tissues compared with corresponding normal mucosal tissues. We also observed that PTBP1 expression levels, c-MYC expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 50 publications
8
62
0
Order By: Relevance
“…This observation is consistent with the findings that hnRNPI is aberrantly expressed in colorectal cancer cells [24,31], and a number of hnRNPI targeting genes are abnormally spliced in colorectal cancer [2430]. While it is possible that the colorectal cancer development in the hnRNPI-deficient mice may be a consequence of impaired neonatal host-microbe homeostasis, it is more likely that hnRNPI plays additional roles in preventing colitis and colorectal cancer development in adulthood.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This observation is consistent with the findings that hnRNPI is aberrantly expressed in colorectal cancer cells [24,31], and a number of hnRNPI targeting genes are abnormally spliced in colorectal cancer [2430]. While it is possible that the colorectal cancer development in the hnRNPI-deficient mice may be a consequence of impaired neonatal host-microbe homeostasis, it is more likely that hnRNPI plays additional roles in preventing colitis and colorectal cancer development in adulthood.…”
Section: Discussionsupporting
confidence: 89%
“…hnRNPI, also known as polypyrimidine tract-binding protein (PTB), plays important roles in alternative splicing and other post-transcriptional regulatory events [22,23]. A number of hnRNPI targets are abnormally spliced in intestinal inflammatory and neoplastic diseases [2431], suggesting that hnRNPI-dependent post-transcriptional control may play important roles in pathogenesis of these diseases. To determine hnRNPI functions in mammalian intestinal homeostasis and more importantly, to understand how malfunction of this protein contributes to inflammation and colorectal cancer, we have generated IEC-specific hnRNPI knockout mice.…”
Section: Introductionmentioning
confidence: 99%
“…4). PTB expression levels are significantly up-regulated in breast, ovarian, glioblastoma, colorectal, and mucosal cancerous tissues compared with the corresponding normal tissues (Jin et al 2000;He et al 2004He et al , 2007He et al , 2014Takahashi et al 2015). PTB controls alternative splicing of target genes, such as pyruvate kinase PKM2 (Clower et al 2010), fibroblast growth factor receptor-1α-exon FGFR-1 (Jin et al 2000), and multidrug resistance protein 1 (MRP1), which contributes to the drug-resistance phenotype associated with many cancers (He et al 2004).…”
Section: Hnrnpk-heterogeneous Nuclear Ribonucleoprotein Kmentioning
confidence: 99%
“…Furthermore, high expression of PTBP1 has been demonstrated to be associated with aggressive behavior of several types of cancer, especially in glioma and ovarian tumors [16, 17]. A recent study showed that PTBP1 mRNA higher expressed in primary colorectal tumor samples than the normal colonic epithelium and indicated poor prognosis [20]. PTBP1 is the critical determinant of PKM embryonic pyruvate kinase isoform 2, which universally over-expressed in cancer for promoting aerobic glycolysis and may affect drug resistance, in transformed cells [2125].…”
Section: Introductionmentioning
confidence: 99%